Lipoprotein associated phospholipase A2 enzyme; possible new roles and inhibition for therapeutic intervention - Tyagi, Manoj G.; Mathew, Sumith K. (International Journal of Research in Medical Sciences, 2017)
Lipoprotein-Associated Phospholipase A2 (Lp-PLA2) is a 45-kDa protein of 441 amino acids encoded by the pla2g7 gene in the humans. In the blood it is associated mainly with Low Density Lipoprotein (LDL) and less than 20% is associated with High Density Lipoprotein (HDL). This enzyme is characterized by its ability to specifically hydrolyze PAF as well as glycerophospholipids containing short, truncated, and/or oxidized fatty acyl groups at the sn-2 position of the glycerol backbone. Genetic studies conducted in humans harboring an inactivating mutation at this locus suggest that loss of Lp-PLA2 function is a risk factor for inflammatory and vascular conditions. Consistently, overexpression of Lp-PLA2 has anti-inflammatory or pro-inflammatory actions and anti-atherogenic properties in animal models. This article discusses two simple techniques to estimate Lp-PLA2 activity. New therapeutic agents inhibiting the activity of Lp-PLA2 are being investigated for curative purpose.